Randomized double-blind trial comparing effects of low-flow vs high-flow anesthesia on postoperative lung functions using respirometer - T Krishna Prasad; N Gnanasekar; K Soundarya Priyadharsini; Robin Sajan Chacko (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Modern anesthetic practice utilizes low-flow anesthesia with evolving evidence on its pulmonary effects. Studies comparing measurement of vital capacity and inspiratory reserve volume using respirometer in both low-flow and high-flow anesthesia are sparse. We evaluated the effects of low-flow and high-flow anesthesia on postoperative pulmonary functions using respirometer. Material and Methods: This was a prospective randomized double blind study wherein One hundred and ten patients undergoing peripheral surgeries under general anesthesia were allocated into two groups Group I- Low-flow anesthesia with O2 + N2O + Sevoflurane (0.5L + 0.5L + 3.5%) and Group II- High-flow anesthesia with O2 + N2O + Sevoflurane (2L + 2L + 2%). The difference in vital capacity (VC), inspiratory reserve volume (IRV), and peak expiratory flow rates (PEFR) from the preoperative period were compared in both the groups postoperatively. Results: The difference in VC, IRV, and PEFR measured in both the groups between the preoperative and postoperative period were found to be similar and statistically insignificant (P - 0.173, 1.00 and 0.213 respectively). The difference in single breath count (SBC), breath holding time (BHT), and respiratory rates (RR) were also similar in both the groups (P - 0.101, 0.698, and 0.467) respectively. Conclusions: The pulmonary effects of low-flow anesthesia are comparable with the high-flow ones in patients undergoing elective surgeries under general anesthesia.